A new measure of fear of falling: psychometric properties of the fear of falling questionnaire revised (FFQ-R). (31st July 2014) - Bower, Emily S.; Wetherell, Julie Loebach; Merz, C. Caroline; Petkus, Andrew J.; Malcarne, Vanessa L.; Lenze, Eric J.
ABSTRACT: Background: Although fear of falling is prevalent among older adults recovering from hip fracture, current instruments are inadequate due to focus on specific situations and measurement of self-efficacy rather than fear. Methods: The authors revised and tested a form of the Fear of Falling Questionnaire with three groups of older adults: 405 recovering from hip fracture, 89 healthy community dwelling, and 42 with severe fear of falling. Test-retest reliability was evaluated in a subsample of 16 hip fracture patients. Internal consistency was compared across all groups. Construct validity was established through factor analysis, convergent validity with a measure of fall-related self-efficacy, and discriminant validity with measures of depression and affect. Results: A revised two-factor, six-item scale appears to have adequate psychometric properties. Scores were lower in the healthy comparison group relative to the hip fracture and fear of falling groups. Cronbach's α ranged from 0.72–0.83, with test-retest reliability of 0.82. Correlations with a measure of fall-related self-efficacy were moderate for the hip fracture group (0.42) and high with the healthy comparison (0.68) and fear of falling (0.70) groups. Correlations with depression and negative and positive affect were low to moderate. Conclusions: The Fear of Falling Questionnaire – Revised shows promise as a self-report measure of fear of falling, and is one of the first to be tested in older adults recovering from hip fracture. Advantages are that it is global rather than situation-specific and measures fear rather than self-efficacy. Future research on this scale is recommended in other older adult samples for whom fear of falling is relevant.